Correlation between prenatal doppler ultrasound exposure durations and newborn rabbit’s body weight - Amran, Umi Nadrah; Ahmad Zaiki, Farah Wahida (Faculty of Medicine and Health Sciences, UPM, 2020)
Introduction: Doppler mode ultrasound is widely used in prenatal scanning and known to produce a higher acoustic output which later leads to higher heat energy conversion compared to other ultrasound modes. It has been reported that the use of Doppler imaging might increase the temperature of tissues, thus, when Doppler is used in combina- tion with 2D ultrasound, the risks of bioeffects tend to increase more. It is also known that prolonged exposure to ultrasound during pregnancy can cause irreversible biological destructions to the fetus. Despite the benefits of using Doppler ultrasound, its potential adverse effects have received scant attention in the research literature. Therefore, this study aimed to examine a correlation between gestational stages (GS) and newborn rabbit’s body weight at differ- ent prenatal Doppler ultrasound exposure durations. Methods: Twelve pregnant New Zealand white rabbits (NZWR) were exposed once using three different Doppler ultrasound exposure durations (30, 60, 90 minutes exposure) at three different GSs (1st, 2nd, and 3rd GS). After delivery, the mean weights of the 62 newborns were statistically ana- lysed. Results: Strong negative and positive correlation between newborn’s body weight at different GSs and Doppler ultrasound exposure durations with a significant result found in 60 minutes exposure (p = <0.01) and 90 minutes exposure (p = <0.01), respectively. Conclusion: It can be concluded that longer Doppler ultrasound exposure may lead to significant results onto the newborn rabbits’ body weight.